THE USE OF SINO-VIETNAMESE IN THE TRANSLATION OF NOUN PHRASES IN HARRY POTTER BOOK SERIES = Nghiên cứu việc sử dụng từ Hán- Việt trong việc dịch các cụm danh từ trong bộ sách Harry Potter - Hoàng, Thị Mỹ Linh (2020)
Translation and its relating issues have become non-stop topics for researchers. Language difference is one of the most basic issues of translation. Aiming at handling the gaps between languages, translation procedures is one of the elements determining the accuracy of language equivalence. Therefore, this research is firstly an attempt to figure out in detail types of translation procedures applied in the Vietnamese version of one of the most famous books for children- Harry Potter book series. By counting the frequency of translation procedures used in the translation of the Vietnamese translator Ly Lan, the characteristics of each procedures affecting the equivalence of the translation are drawn, in which through translation, functional equivalence, and couplet are most frequently used. Together with that, the Sino-Vietnamese structures used in the books are also concentrated in the hope to have a deeper look into the use of Sino-Vietnamese in the translation of literary documents. By modeling common Sino-Vietnamese structures of noun phrases in Ly Lan’s versions, some structures are built, including some stylistic structures of the translator such as “Bất khả+V”, or “V+N-career indicator”. In comparison with original noun phrases, some features of Sino-Vietnamese are also described. One of those is the ability to remain the structure of English noun phrase by using the structure “N Adj+N” or “N Q+ N”. Basing on the closeness in structures of phrases, Sino-Vietnamese must be exploited in other literary documents and fictions as well. Last but not least, since the suggestions were given basing on a small-scale study, the answer to it needs more examination, thus requires larger-scale studies. Further studies should be of larger scope to increase the validity as well as reliability of the results. More discussions are needed within the topic of translation procedures and the use of Sino-Vietnamese, as there remain a lot of issues to discover.